Dienylation of N-benzoylhydrazones with CF3-substituted homoallenylboronates in water. Issue 7 (28th January 2022) - Ma, Wei-Wei; Yang, Chao; Xie, Qiang; Xu, Yun-He
Abstract : A convenient method for the dienylation of N -benzoylhydrazones in water has been developed. Abstract : A convenient method for the dienylation of N -benzoylhydrazones in water has been developed. This protocol expanded the synthetic application of functionalized homoallenylboronates to provide the useful 2-aminomethyl-1, 3-diene derivatives with high efficiency (up to 99% yield) and stereoselectivity without using any catalyst, additive or inert atmosphere. Furthermore, the transformation of a 2-aminomethyl-1, 3-diene derivative to synthesize a functionalized pyrrolidine derivative was also explored.